Acute Hepatitis of Unknown Etiology Among Young Children: Research Agenda by the ESPGHAN Hepatology Committee. Issue 4 (20th September 2022) - Indolfi, Giuseppe; Czubkowski, Piotr; Fitzpatrick, Emer; Gonzales, Emmanuel; Gupte, Girish; Mancell, Sara; Mozer-Glassberg, Yael; Nicastro, Emanuele; Norman, Junge; Stephenne, Xavier; Zellos, Aglaia; Samyn, Marianne
Abstract : In April 2022, an increased incidence of acute hepatitis cases of unknown etiology among previously healthy children across the United Kingdom was described. Since, more than 270 cases from the United Kingdom and hundreds more from all across the world have been reported. The majority of affected children were younger than 6 years of age. The clinical presentation was nonspecific with diarrhea and vomiting usually preceding the appearance of jaundice, abdominal pain, nausea, and malaise. Approximately 5% have required liver transplantation. An infectious etiology has been considered likely given the epidemiological and clinical features of the reported cases. Between 50 and 60% of the children tested were diagnosed with adenovirus infection although a clear etiological connection has still to be demonstrated. No link with SARS-CoV-2 infection and COVID-19 vaccine was found. What is not clear to date is whether the high number of acute hepatitis cases reported is related to a true increase in incidence or heightened awareness following on from the initial reports from the United Kingdom. The Hepatology Committee of the European Society of Pediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) developed a paper on the current outbreak of acute hepatitis of unknown etiology recognizing its importance and the need of approaching the current situation with a scientifically rigorous approach. The aims of the article are to summarize the current knowledge and to identify the most pertinent issues regarding the diagnosis and management of this condition and the research questions raised.